2016
DOI: 10.1111/resp.12930
|View full text |Cite
|
Sign up to set email alerts
|

Association between asthma control and asthma cost: Results from a longitudinal study in a primary care setting

Abstract: Background and objective: Asthma control can be assessed with the Asthma Control Test (ACT) and a score of 20 or higher indicates good asthma control. Patients pay for their consultation and treatment in the fee-for-service primary healthcare system in Singapore. We hypothesized that achieving asthma control would result in lower asthma costs through reduced acute exacerbations, fewer physician consultations and lower lost productivity. The study compared the healthcare costs of patients who achieved asthma co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…In total, six studies reported on costs [50,65,70,[76][77][78], of which five reported relationships between asthma control subgroup and direct medical costs [50,65,70,76,77], and three with indirect medical costs [65,77,78]. However, only one study reported statistically significant results for direct medical costs [77].…”
Section: Act Score and Resource Use And Costsmentioning
confidence: 99%
“…In total, six studies reported on costs [50,65,70,[76][77][78], of which five reported relationships between asthma control subgroup and direct medical costs [50,65,70,76,77], and three with indirect medical costs [65,77,78]. However, only one study reported statistically significant results for direct medical costs [77].…”
Section: Act Score and Resource Use And Costsmentioning
confidence: 99%
“…Further, different studies have used different definition of asthma control (e.g., based on cut-offs on the ACT test or symptom control as defined by Global Initiative for Asthma). While we attempted to use a consistent definition of control, the availability of evidence forced us to relax this assumption at times; for example, in estimating the association between outcomes and controlled levels, we considered other definitions of asthma control ,such as Global Initiative for Asthma(GINA) and National Asthma Education and Prevention Program (NAEPP) as equivalent of ACT in three studies (8,34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Achieving asthma control is associated with improvement in quality of life, reduction in medical costs, and better work performance (7,8). Unfortunately, the reality of asthma care is highlighted by poor adherence to treatments and other disease management modalities (e.g., avoidance of triggers), resulting in a significant proportion of asthma patients experiencing suboptimal asthma control (9).…”
Section: Introductionmentioning
confidence: 99%
“…Admittedly, medication costs were greater for patients with asthma and COPD visiting specialists versus GP. However, prior work suggests that patients with good asthma control may incur greater drug costs, but optimal asthma control is associated with lower overall asthma-related costs than suboptimal asthma control [42]. Criteria for referral to specialists are important components to include in practice guidelines [43].…”
Section: Discussionmentioning
confidence: 99%